2020
DOI: 10.1007/s42452-020-2488-7
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the stability of ligand-protected Au nanoclusters under electrochemical reduction of CO2

Abstract: Ligand-protected gold nanoclusters are a novel class of particles that have attracted great interest in the field of catalysis due to their atomically-precise structure, high surface-to-volume ratio, and unique electronic properties. In particular, the anionic thiolate-protected Au 25 nanocluster (NC), [Au 25 (SR) 18 ] 1− , with partially lost ligands, has been demonstrated to act as an active catalyst for the electrochemical reduction of CO 2. However, the stability of this and other thiolate-protected NCs af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
3
25
0
Order By: Relevance
“…We observed that it is more thermodynamically feasible to remove the ‐R group as compared to the ‐SR group from both NCs. This is consistent with previous work that reported the ease of exposing a sulfur atom (‐R group removal, R=CH 3 ) as an active site compared to gold (‐SR removal) from the [Au 25 (SCH 3 ) 18 ] 1− nanocluster [26c] . Cleaving a ‐R group from either nanocluster was nearly thermoneutral, implying that the thermodynamics of formation of the S active site is similar on both NCs.…”
Section: Figuresupporting
confidence: 91%
“…We observed that it is more thermodynamically feasible to remove the ‐R group as compared to the ‐SR group from both NCs. This is consistent with previous work that reported the ease of exposing a sulfur atom (‐R group removal, R=CH 3 ) as an active site compared to gold (‐SR removal) from the [Au 25 (SCH 3 ) 18 ] 1− nanocluster [26c] . Cleaving a ‐R group from either nanocluster was nearly thermoneutral, implying that the thermodynamics of formation of the S active site is similar on both NCs.…”
Section: Figuresupporting
confidence: 91%
“…The relaxed structures of the NCs obtained from DFT are similar to the experimentally obtained structures (Figure S3). A common approach to reduce the computational expense while still accurately capturing the catalytic activity trends of NCs is to replace the experimental bulky ligands such as SPhMe 2 with SCH 3 groups. ,, Here we use the same approach for DFT calculations. Previous studies have shown that removing a ligand under reaction conditions is feasible and can lead to the creation of active sites for catalysis. , Using the fully relaxed structures, we calculate the Gibbs free energy (Δ G ) of removing either the −R (−CH 3 ) group or the −SR (−SCH 3 ) group, which leads to the exposure of a sulfur or metal atom, respectively, as an active site.…”
Section: Resultsmentioning
confidence: 99%
“…A common approach to reduce the computational expense while still accurately capturing the catalytic activity trends of NCs is to replace the experimental bulky ligands such as SPhMe 2 with SCH 3 groups. 22,29,30 Here we use the same approach for DFT calculations. Previous studies have shown that removing a ligand under reaction conditions is feasible and can lead to the creation of active sites for catalysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Several recent DFT calculations have predicted that higher activity can be achieved through the elimination of ligands also in the application of metal NCs as electrocatalysts. [337][338][339][340][341][342] However, there are also reactions in which the presence of ligands leads to an improvement of the conversion efficiency. In addition, the presence of ligands has advantages in changing the reaction selectivity and suppressing aggregation of metal NCs, thereby improving the catalyst durability.…”
Section: Necessity Of Ligand Eliminationmentioning
confidence: 99%
“…For such heterogeneous catalysts composed of atomically precise metal NCs, DFT calculations may be able to predict highly functional catalyst systems. [337][338][339][340][341][342]348 Thus, in the future, it is expected that studies for improving the functionality of heterogeneous catalysts will shift from searching for the optimum system based on trial-and-error experiments to prediction by DFT calculation.…”
Section: Guidance By Dft Calculationmentioning
confidence: 99%